PENGENDALIAN PERALATAN RUMAH TANGGA MENGGUNAKAN ARDUINO UNO BERBASIS BLUETOOTH - Fauzi, Ahmad; Rijanto, Tri; Kurniadi Wardana, Humaidillah (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
With increasing preoccupation of mankind it takes a smart home system innovation which is the concept of home automation control device comprising of a smartphone. Smart home system aims tofacilitate the work of humans in controlling household appliances using a smartphone. The research method used is the method of measurement of the distance to reach. On the sensor LightDependent Resistor (LDR) and method of reading the average light intensity on the morning and afternoon.A method of Passive Infrared sensor on Receaver (PIR) by detecting the distance sensitivity of humanmovement response. The results showed the distance which can be reached by a hc-05untuk bluetooth to control the lightsand the fan as far as 75 metres to condition without hindrance, while sensors LDR with an average 20.5 luxin the morning while in the evening with an average 19.5 lux, sensor PIR respond to human movement asfar as 7 meters. Keywords: Bluetooth hc-05, Smart home, Sensor Light Dependent Resistor (LDR), Infrared Sensor Receaver (PIR)